Analisis Kinerja Ekspor alas kaki Indonesia ke kawasan ASEAN: Institut Pertanian Bogor - Widya Nadira Nasution; Sri Mulatsih (IPB University, 2019)
The main export of Indonesian footwear is to the United States and several countries in Europe, while for the nearest region to Indonesia, such as ASEAN, the export value of Indonesian footwear is quite low. This study aims to analyze the competitiveness and performance of Indonesian footwear exports to the ASEAN region in 2010-2014. The partner countries in this study are Malaysia, Singapore, Thailand, the Philippines, Vietnam, and Brunei Darussalam. Competitiveness analysis is carried out using Revealed Comparative Advantages (RCA), Porter's Diamond, and Export Product Dynamic (EPD) indicators. The results of the RCA analysis show that Indonesian footwear has competitiveness in all countries except for Malaysia. The results of the Porter's Diamond model show that Indonesia has strong competitiveness in the footwear sector. The results of the EPD analysis show that the footwear export to the majority of partner countries are in falling star criteria. Furthermore, the analysis of footwear exports performance to the ASEAN region is carried out using the Gravity Model. The results of the analysis show that all variables significantly affect the footwear export performance. Indonesia's GDP per capita, economic distance, and export prices have negative effect on export performance, while GDP per capita of partner countries has positive effect. Exchange rate depreciation has positive impact on improving export performance.